Governance institutions and prospects for local energy innovation: laggards and leaders among UK local authorities. (March 2020) - Tingey, Margaret; Webb, Janette
Abstract: UK Local Authorities are increasingly declaring 'climate emergencies' and pledging 100% clean energy and carbon neutrality ambitions for their locality, despite lack of powers over energy systems. Our research investigates current Local Authority engagement in clean energy, and considers prospects for meso-scale innovation. The analysis allocates Local Authorities to one of four categories of engagement, from energy 'laggards' through to 'leaders', based on their energy plans and investments. Findings reveal that, despite lack of direct powers, a high proportion of Local Authorities have developed sustainable energy plans and projects, but only a minority manage to combine these into a more strategic local programme. There was proportionately greater activity in Scotland and considerable variation was found across English regions. We conclude that variation in levels of engagement relates to authority size and divisions of responsibilities between different levels of government. The capacity for Local Authority-mediated social innovation to support development of a clean UK energy system is discussed. Implications for policy include the need for a statutory power, and commensurate resources, for Local Authorities, to ensure a more comprehensive and systematic contribution to clean energy innovation. Highlights: This paper investigates UK Local Authorities' (LAs) clean energy initiatives. Many LAs developed sustainable energy plans and projects, but only a minority evidenced a strategic local energy programme. Proportionately greater activity was found in Scotland than in England, Wales and Northern Ireland. Considerable variation was found across English regions and local government structures. Divergent pathways are emerging within the UK, signalling differentiation of local energy innovation trajectories.